The modern wheelset drive system and possibilities of modelling the torsion dynamics - Lata, Michael (Transport, 2008)
The article deals with the view of modern wheelset drive construction design in the first part. Next part deals with dynamics of the wheelset individual drive torsion system in electric traction vehicles, explained by the drive model in several variants. The basics of time simulation of the transition dynamics effects have been explained and the frequency analysis of the system has been shown. Identification of transition dynamics effects in the wheelset drive enables to evaluate precisely the loading on individual parts during the design stage, to apply the results in anti‐skid protection and probably also to disclose some effects due to wear in the wheel‐rail contact. First published online: 27 Oct 2010